Community Empowerment In Palaes Tourism Village, West Likupang District - Drevy Dallesandry Malalantang (Jurnal Mamangan, 2025)
Community empowerment is crucial for the sustainability of a village, especially a tourism village. The community is the core of development, ensuring that a tourism village is not merely a temporary viral phenomenon but can thrive long-term by involving the community as the primary foundation, rather than focusing on outsiders. This ensures that the community is not colonized within its own village and can generate its own income. The goal of developing tourism villages through the community is essentially to ensure the economic sustainability of the tourism village itself. From the community, to the community, and for the community. The purpose of this research is to understand community empowerment (enabling, empowering, protecting) or providing, empowering, and protecting.This research was conducted in Palaes Tourism Village, West Likupang District. The research method used in this study is a descriptive qualitative method, namely data in the form of a collection of words, images, videos, recordings, and not numbers. The research instruments were the Palaes village government (Old Law, Old Law Secretary, Director of Bumdes) and the community (members of MSMEs, ordinary people) and also tourists as supporting factors. The research was conducted for 6 months, from May 2023 to December 2023. Data were obtained through observation, interviews, and documentation.The results of this study conclude that enabling (providing) the government successfully provides support in various ways for the advancement of tourist villages, so that the community can recognize the potential of the village and the potential of human resources (HR) itself, namely by building cooperation with various parties to achieve the necessary facilities. Empowering (empowering), the government empowers the community through Village-Owned Enterprises (BUMDES), namely by becoming members of MSMEs, handicrafts, and becoming homestay managers. According to the interview results, only 30% of the community is directly involved in empowerment, the rest is still being worked on by the government. Protecting (protecting), the government's way of protecting the Palaes tourist village system is twofold: external protection, namely by being very selective in choosing future investors. Do not let investors be more important than the community itself, especially if it is colonized in the village itself. Next, internal protection, namely by always maintaining good relations with the Palaes tourist village community, both those directly involved and those who have not been involved/have not yet involved themselves in the development of the tourist village. The government considers maintaining harmony between the government and the community and between communities is paramount to prevent conflicts that break the system. In addition, the government also protects the system by providing firmness and sanctions to people who violate the rules.